Intellectual property rights, migration, and diaspora - Alireza Naghavi; Chiara Strozzi (Institute for the Study of Labor (IZA), 2011)
In this paper we study theoretically and empirically the role of the interaction between skilled migration and intellectual property rights (IPRs) protection in determining innovation in developing countries (South). We show that although emigration from the South may directly result in the well-known concept of brain drain, it also causes a brain gain effect, the extent of which depends on the level of IPRs protection in the sending country. We argue this to come from a diaspora channel through which the knowledge acquired by emigrants abroad can flow back to the South and enhance the skills of the remaining workers there. By increasing the size of the innovation sector and the skill-intensity of emigration, IPRs protection makes it more likely for diaspora gains to dominate, thus facilitating a potential net brain gain. Our main theoretical insights are then tested empirically using a panel dataset of emerging and developing countries. The findings reveal a positive correlation between emigration and innovation in the presence of strong IPRs protection.
urn:nbn:de:101:1-201108092913
Keywords: O34; F22; O33; J24; J61; 330; intellectual property rights; migration; technology transfer; brain gain; diaspora